2018
DOI: 10.1161/strokeaha.118.020788
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Infarct Growth and Secondary Injury Volumes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…As previously observed, in our model ( Debatisse et al , 2020 ), acute infarcts were generally not as massive as in human ischaemic stroke limiting the occurrence of malignant oedema, and the few cases with very large lesion died prematurely. With no massive oedema at Day 7, the non-linear registration performed well to correct for minor oedema as observed in our previous study ( Debatisse et al , 2020 ) and as also demonstrated in clinical data ( Harston et al , 2018 ). Between Day 7 and Day 30, there is substantial infarct size reduction but the tissue loss in the ipsilateral hemisphere was not large enough to disturb the non-linear registration to the template space.…”
Section: Discussionsupporting
confidence: 83%
“…As previously observed, in our model ( Debatisse et al , 2020 ), acute infarcts were generally not as massive as in human ischaemic stroke limiting the occurrence of malignant oedema, and the few cases with very large lesion died prematurely. With no massive oedema at Day 7, the non-linear registration performed well to correct for minor oedema as observed in our previous study ( Debatisse et al , 2020 ) and as also demonstrated in clinical data ( Harston et al , 2018 ). Between Day 7 and Day 30, there is substantial infarct size reduction but the tissue loss in the ipsilateral hemisphere was not large enough to disturb the non-linear registration to the template space.…”
Section: Discussionsupporting
confidence: 83%
“…However, vasogenic edema usually occurs in the first week and can artificially inflate lesion volume. Previous studies demonstrated that 24 h evaluation of infarct volume by non-contrast computed tomodensitometry is as well correlated to 3 month-mRS than is 1 week evaluation ( 59 , 60 ). There is currently no consensus about the best time-point to evaluate infarct growth, and future stroke studies are needed to address this issue.…”
Section: Discussionmentioning
confidence: 98%
“…13 In addition, in these studies, true lesion growth was not distinguished from edema, although the latter may account for up to one-third of the lesion volume. 3,4,23 The use of a nonlinear coregistered MRI approach may limit this bias.…”
Section: Discussionmentioning
confidence: 99%